2023
DOI: 10.3390/agronomy13020519
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tandem Zinc Finger Protein in Gossypium hirsutum, GhTZF2, Interacts with GhMORF8 to Regulate Cotton Fiber Cell Development

Abstract: Arginine-rich Tandem Zinc Finger (RR-TZF) proteins make up a plant-specific superfamily that participates in plant development, while their roles in cotton fiber development remain to be explored. In this study, we identified an RR-TZF protein-coding gene, GhTZF2, containing two CCCH domains (C-X7-C-X5-C-X3-H-X16-C-X5-C-X4-C-X3-H) and one RR domain at the N-terminus of the two CCCH domains, by comparing the differences of chromatin H3K4me3 modifications between wild-type upland cotton (WT) and the fuzzless-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…6C). Among which, the autoinhibited Ca 2+ -ATPase genes ACA11 and ACA9 encoding calcium pumps (Li et al, 2023), KAT3 encoding a subunit of potassium channel (Sun et al, 2015), ARP1 encoding an ABA-regulated RNA-binding protein 1 (Jung et al, 2013), and Hsp90.5 encoding a heat shock protein (Song et al, 2009) are all implicated in playing a negative role in salt stress tolerance response. RIP-qPCR results showed that TZF1, but not the TZF H186Y , could bind the F1 region of ACA11 mRNA (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6C). Among which, the autoinhibited Ca 2+ -ATPase genes ACA11 and ACA9 encoding calcium pumps (Li et al, 2023), KAT3 encoding a subunit of potassium channel (Sun et al, 2015), ARP1 encoding an ABA-regulated RNA-binding protein 1 (Jung et al, 2013), and Hsp90.5 encoding a heat shock protein (Song et al, 2009) are all implicated in playing a negative role in salt stress tolerance response. RIP-qPCR results showed that TZF1, but not the TZF H186Y , could bind the F1 region of ACA11 mRNA (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…One potential candidate is ACA11 (Fig. 6C), a tonoplast-localized Ca 2+ pump (like ACA4 ) (Li et al, 2023). Salt stress is known to result in Ca 2+ accumulation in the cytoplasm where it functions as an important secondary messenger to trigger a complex signal transduction pathway to enhance salt stress tolerance (Zhao et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the operation of similar mechanisms for fiber initiation in these two fiberless lines. The study sheds light on the regulatory networks mediated by GhMML3 and GhVIN1 in controlling fiber initiation in cotton [33].…”
Section: Fiberless Mutants Identificationmentioning
confidence: 90%
“…Comparative transcriptome analysis between the natural fiberless mutant XZ142FLM and the transgenic fiberless line GhVIN1i, obtained by RNAi silencing of GhVIN1, identified common differentially expressed genes (DEGs) in ovules during fiber initiation. The respective DEGs were enriched in several identical pathways related to fiber initiation, revealing shared molecular regulatory networks controlling fiber initiation [33]. Several genes related to fiber initiation or elongation, such as GhMML3, GhVIN1, GhMYB25, GhHD-1, and GhHOX3, exhibited similar expression patterns in mutant XZ142FLM and the RNAi mutant GhVIN1i during fiber early development.…”
Section: Fiberless Mutants Identificationmentioning
confidence: 93%
See 1 more Smart Citation